Bus rapid transit and the transformation of the urban space in Bogotá and Ahmedabad (2018)
The study of cities from an interdisciplinary perspective, implies to consider the power structures, synergies and relationships between multiple actors who are shaping the built environment where we live in. Within this frame, the spatial political economy in the urban planning discipline develops multiple approaches, which aim fundamentally to understand the forces shaping the structure and power relations in cities (Cuthbert, 2008). This is the case of the provision of urban transport infrastructure, which has played a key role in the understanding of the political economy of cities and space. From an urban design perspective, the production of public space, including transportation investments, is part of the public realm. Location within cities and space is also part of the multiple ways in which the State seeks the control of space to promote the development of the private sector and labour. Hence, the provision of multiple transportation modes is crucial in this type of control.